Prediction of H3K27M mutation status of diffuse midline gliomas using MRI features. Issue 6 (29th June 2021) - Chauhan, Richa Singh; Kulanthaivelu, Karthik; Kathrani, Nihar; Kotwal, Abhishek; Bhat, Maya Dattatraya; Saini, Jitender; Prasad, Chandrajit; Chakrabarti, Dhritiman; Santosh, Vani; Uppar, Alok Mohan; Srinivas, Dwarakanath
Abstract: Background and Purpose: Presurgical prediction of H3K27M mutation in diffuse midline gliomas (DMGs) on MRI is desirable. The purpose of this study is to elaborate conventional MRI (cMRI) features of H3K27M‐mutant DMGs and identify features that could discriminate them from wild‐type (WT) DMGs. Methods: CMRI features of 123 patients with DMG were evaluated conforming to the institutional research protocols. Multimodality MRI was performed on 1.5 or 3.0 Tesla MR Scanners with imaging protocol, including T1‐weighted (w), T2w, fluid‐attenuated inversion recovery, diffusion‐weighted, susceptibility‐weighted, and postcontrast T1w sequences. Pertinent cMRI features were annotated along the lines of Visually AcceSAble Rembrandt Images features, and Intra Tumoral Susceptibility Signal score (ITSS) was evaluated. R software was used for statistical analysis. Results: Sixty‐one DMGs were H3K27M‐mutant (mutant DMGs). The patients in the H3K27M‐mutant DMG group were younger compared to the WT‐DMG group (mean age 24.13 ± 13.13 years vs. 35.79±18.74 years) ( p = 0.016). The two groups differed on five cMRI features––(1) enhancement quality ( p = 0.032), (2) thickness of enhancing margin ( p = 0.05), (3) proportion of edema ( p = 0.002), (4) definition of noncontrast‐enhancing tumor (NCET) margin ( p = 0.001), and (5) cortical invasion ( p = 0.037). The mutant DMGs showed greater enhancement and greater thickness of enhancing margin, while the WT DMGs exhibited significantly larger edema proportion with poorly defined NCET margins and cortical invasion. ITSS was not significantly different among the groups. Conclusion: CMRI features like enhancement quality, the thickness of the enhancing margin, proportion of edema, definition of NCET margin, and cortical invasion can discriminate between the H3K27M‐mutant and WT DMGs.